2022
DOI: 10.1111/jog.15446
|View full text |Cite
|
Sign up to set email alerts
|

No significant changes in preterm birth, low‐birth‐weight, and small‐for‐gestational‐age infants during the first year of the COVID‐19 pandemic in a rural area in Japan

Abstract: Aims: To evaluate the coronavirus disease 2019 pandemic's impact on pregnancy outcomes in a Japanese rural area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…However, the results are still contradictory in Japan. Ohashi et al 17 analyzed data from an epidemiological receipt database and showed an increasing trend of HDP but with no significant difference, similar to our findings; in contrast, other studies detected a reduction in HDP 13 15 . Few previous studies have assessed the impact of FGR in Japan.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, the results are still contradictory in Japan. Ohashi et al 17 analyzed data from an epidemiological receipt database and showed an increasing trend of HDP but with no significant difference, similar to our findings; in contrast, other studies detected a reduction in HDP 13 15 . Few previous studies have assessed the impact of FGR in Japan.…”
Section: Discussionsupporting
confidence: 87%
“…However, few studies have reported the impact of the pandemic on pregnancy outcomes in Japan. Maki et al 13 analyzed the rates of preterm delivery, low birth weight (LBW) infants, and small-for-gestational-age infants during the first year of the pandemic compared to those in the preceding 3 years and found no significant changes. However, the results were limited to a local area in Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are some studies that investigated trends in adverse birth outcomes and fetal mortality over the decades in Japan using national data [ 5 , 6 , 17 ], while such studies did not evaluate the effect of the pandemic. Moreover, there are some studies that investigated an effect of the pandemic on adverse birth outcomes or threatened preterm labor in Japan [ 18 23 ]. In contrast, the sample size used in each study was relatively small, and it is meaningful to evaluate an effect of the pandemic on the adverse outcomes using nationwide national data in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, only a limited number of studies indicated an overall increase in PTD [43,44]. Studies that included some 2021 data also reported an increase [45,46] or no significant changes in PTD [47] and SGA [48] compared to pre-pandemic rates within their respective populations.…”
Section: Discussionmentioning
confidence: 99%